2015
DOI: 10.1007/s13105-015-0413-0
|View full text |Cite
|
Sign up to set email alerts
|

A signature of microRNA-155 in the pathogenesis of diabetic complications

Abstract: The current study was designed to explore the potential involvement of miR-155 in the pathogenesis of diabetes complications. Male rats were divided into control and diabetic groups (n = 6). Type 2 diabetes was induced by a single-dose injection of nicotinamide (110 mg/kg; intraperitoneal (i.p.)), 15 min before injection of streptozotocin (STZ; 50 mg/kg; i.p.) in 12-h fasted rats. Two months after induction of diabetes, the rats were sacrificed for subsequent measurements. The nuclear factor kappa B (NF-κB) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Moreover, miR-155-5p positively regulates host antiviral immune response by promoting type I IFN signaling through targeting SOCS1, a negative regulator of the type I IFN pathway [47]. Consequently, miR-155-5p dysregulation has been associated with different cancers, cardiovascular diseases, viral infections, rheumatoid arthritis, and chronic diabetic complications [45,46,48].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-155-5p positively regulates host antiviral immune response by promoting type I IFN signaling through targeting SOCS1, a negative regulator of the type I IFN pathway [47]. Consequently, miR-155-5p dysregulation has been associated with different cancers, cardiovascular diseases, viral infections, rheumatoid arthritis, and chronic diabetic complications [45,46,48].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, mRNA expression and function are susceptible to environmental factors, especially hyperglycemic conditions, which usually further result in disease complications. In addition, platelet and plasma miR-144 and miR-223 have been shown to be significantly altered in type 2 diabetes mellitus (T2DM) patients [5]; changes in the expression of miR-155 may play a role in the pathogenesis of diabetes-related complications [6]. Studies have shown that miR-3202 is downregulated in patients with early-onset post-stroke depression [7], that its expression is upregulated by radon in the lung BEAS-2B cell line [8], and that it is upregulated as secreted miRNAs isolated from LNCaP prostate cancer cells compared with normal human prostate epithelial cells (PrECs) [9].…”
Section: Introductionmentioning
confidence: 99%
“…16,17,18,19,20,21,22,23,24 The dysregulation of miR-155 has recently been reported to play important roles in multiple cardiovascular diseases like atherosclerosis, hypertrophic cardiac remodeling, acute myocardial infarction, myocardial ischemia-reperfusion injury, and diabetic cardiomyopathy. 25,26,27,28,29,30 Additionally, miR-155 is a well-known immunomodulatory miRNA that can be induced by lipopolysaccharide (LPS) and control inflammatory processes in multiple cells and organs. 31,32,33,34 However, the role of miR-155 in sepsis-induced myocardial dysfunction remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%